2013
DOI: 10.1007/s00299-012-1377-y
|View full text |Cite
|
Sign up to set email alerts
|

Differential induction of oxylipin pathway in potato and tobacco cells by bacterial and oomycete elicitors

Abstract: Potato and tobacco cells are differentially suited to study oxylipin pathway and elicitor-induced responses. Synthesis of oxylipins via the lipoxygenase (LOX) pathway provides plant cells with an important class of signaling molecules, related to plant stress responses and innate immunity. The aim of this study was to evaluate the induction of LOX pathway in tobacco and potato cells induced by a concentrated culture filtrate (CCF) from Phytophthora infestans and lipopolysaccharide (LPS) from Pectobacterium atr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…PAMPs are conserved pathogen‐derived molecules that are essential to the pathogen's survival or lifestyle (Gómez‐Gómez, ) and trigger a number of general defence responses, including the biosynthesis of reactive oxygen species (ROS), cell wall reinforcement (callose deposition) and induction of defence gene expression (Garcia‐Brugger et al ., ; Ingle et al ., ). They also activate several metabolic pathways leading to the biosynthesis of phenylpropanoids (Kröner et al ., ), oxylipins (Saubeau et al ., ) or sesquiterpenoids (Yoshioka et al ., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PAMPs are conserved pathogen‐derived molecules that are essential to the pathogen's survival or lifestyle (Gómez‐Gómez, ) and trigger a number of general defence responses, including the biosynthesis of reactive oxygen species (ROS), cell wall reinforcement (callose deposition) and induction of defence gene expression (Garcia‐Brugger et al ., ; Ingle et al ., ). They also activate several metabolic pathways leading to the biosynthesis of phenylpropanoids (Kröner et al ., ), oxylipins (Saubeau et al ., ) or sesquiterpenoids (Yoshioka et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously demonstrated that a recently characterized concentrated culture filtrate (CCF) of P. infestans (Saubeau et al, 2014) can be considered as a PAMP (Desender et al, 2006). The CCF primes defence reactions in potato cell suspensions (Val et al, 2008) and triggers accumulation of various oxylipins in tobacco and potato cell suspensions (Saubeau et al, 2013). It was also shown that, in five potato genotypes with different levels of quantitative resistance to P. infestans, the CCF also induced the phenylpropanoid pathway (Kr€ oner et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…27 Interestingly, the induction of PAL1 transcript seemed to be correlated with the LPS-induced ROS generation, since PAL1 transcription after treatment with LPS Pcc was larger at 1 h than at 3 h on the opposite of what observed with LPS P. aeruginosa . Tiron, a scavenger of ROS, as well as DPI were able to decrease ROS generation and the LPS-induced PAL1 transcription.…”
Section: Discussionmentioning
confidence: 94%
“…26 The fact that LPS induced variable cellular responses can be attributed to LPS preparations, plants and cell types used and reflect the ability of particular plants to recognize structural features within LPS that are not widely conserved. 14,27 [28][29][30] Also, depending on animal model and cell type, LPS could acts as mechanism of protection and preventing cell death, 31 or virulence factors by favoring the escape from the innate immune system. 32 Thus, LPS could have complex and different roles in plants as well as in animals.…”
Section: Introductionmentioning
confidence: 99%
“…This enzyme was chosen as a general defence marker governing diverse defence pathways (oxylipins, phenylpropanoids, etc. ), triggered either directly or through hormonal regulation, and involved in soft rot restriction in potato (Desender et al, 2006;Kr€ oner et al, 2011Kr€ oner et al, , 2012Saubeau et al, 2013Saubeau et al, , 2016.…”
Section: Introductionmentioning
confidence: 99%